THE IMPLEMENTATION OF SPEAKING STRATEGIES IN DEVELOPING STUDENTS’ COMMUNICATIVE COMPETENCE - Sodiqova Sayyora, Sodiqova Sayyora (Журнал иностранных языков и лингвистики, 2021)
Speaking is a crucial part of second language learning and teaching. Despite its importance, for many years, teaching speaking has been undervalued and English language teachers have continued to teach speaking just as a repetition of drills or memorization of dialogues. However, today’s world requires that the goal of teaching speaking should improve students’ communicative skills, because, only in that way, students can express themselves and learn how to follow the social and cultural rules appropriate in each communicative circumstance. In order to teach second language learners how to speak in the best way possible, some speaking activities are provided, that can be applied to ESL and EFL classroom settings, together with suggestions for teachers who teach oral language.